SsUbc2, a determinant of pathogenicity, functions as a key coordinator controlling global transcriptomic reprogramming during mating in sugarcane smut fungus - Lu, Shan; Zhang, Haoyang; Guo, Feng; Yang, Yanfang; Shen, Xiaorui; Chen, Baoshan (Frontiers in Microbiology, 2022)
The basidiomycete fungus Sporisorium scitamineum is the causative agent of sugarcane smut disease. Mating between two strains of the opposite mating type is essential for filamentous growth and infection in sugarcane plants. However, the mechanisms underlying mating and pathogenicity are still not well understood. In this work we used gene disruption to investigate the role of Ssubc2, the gene encoding a kinase regulator in S. scitamineum. Deletion of Ssubc2 did not alter the haploid cell morphology or growth rate in vitro or tolerance to stress, but mutants with both alleles deleted lost mating ability and infectivity. Deletion of one Ssubc2 allele in a pair with a wild-type strain resulted in impaired mating and reduced virulence. Transcriptome profiling revealed that about a third of genes underwent reprogramming in the wild types during mating. Although gene expression reprogramming occurred in the pairing of Ssubc2-null mutants, their transcriptomic profile differed significantly from that of the wild types, in which 625 genes differed from those present in the wild types that seemed to be among the required genes for a successful mating. These genes include those known to regulate mating and pathogenicity, such as components of the MAPK pathway and hgl1. Additionally, a total of 908 genes were differentially expressed in an out-of-control manner in the mutants. We conclude that SsUbc2 functions as a key factor to coordinate the reprogramming of gene expression at the global level and is essential for the transition from monokaryotic basidial growth to dikaryotic hyphal growth through mating.